Attitudes and knowledge of the Greek nursing students towards older people - Sourtzi, Panayota A.; Kalokerinou, Athena; Lambrinou, Ekaterini (My University, 2009)
The proportion of older people has increased worldwide and so are the health problems related with ageing, such as cardiovascular diseases and cancer that often need long-term nursing care. Nurses therefore, have a pivotal role in the care of older people. AIM: To evaluate the effects of education on nursing students' knowledge and attitudes towards older people in Greece. METHOD: Two hundred and twenty seven first and final year nursing students at a university and 191 first and final year nursing students at a Technological Education Institute completed a questionnaire, including demographic questions, the Kogan's Old People Scale and the Palmore's Facts on Aging Quiz I. RESULTS: Attitudes towards older people were more positive in final year students in comparison to first year ones in both schools. Knowledge was found better only in relation to physical health in the final year students, in both schools. Age and female gender were found to influence both attitudes and knowledge positively. CONCLUSIONS: Nursing education in Greece seems to influence the attitudes and knowledge of nursing students towards older people. However, revisions and improvements in curricula are needed if nursing students are to gain a more holistic perspective of older people.
Keywords: Attitudes; Knowledge; Nursing students; Older people